STUDI AGAMA PENDEKATAN HISTORIS: SEBUAH UPAYA MENANGKAL INTOLERANSI BERAGAMA - Estomihi Hutagalung (Majalah Ilmiah METHODA, 2018)
In contemporary religious discourse, it has raised awareness that religious study is not only dealing with the issue of divinity but are related to the social reality of society as its historical context. Such awareness demands and makes historical context an important factor in religious study to understand the sacred message of religious teachings. Then religious studies, aside from being an attempt to understand God's will, also born from the reality of historical context. So that the lecturers (teachers, lecturers, preacher, ulama) of religious study must be able to understand the historical context of the birth of religious texts and understand the historical context of their teaching in the frame of religious pluralism in Indonesia. With this method, as evidenced in the history of religious encounter with its historical reality, it will be able to counteract cases of violence and be able to realize the sacred value of religion in maintaining the harmony of religious people in Indonesia